2016
DOI: 10.1093/nar/gkw353
|View full text |Cite
|
Sign up to set email alerts
|

Imino proton NMR guides the reprogramming of A•T specific minor groove binders for mixed base pair recognition

Abstract: Sequence-specific binding to DNA is crucial for targeting transcription factor-DNA complexes to modulate gene expression. The heterocyclic diamidine, DB2277, specifically recognizes a single G•C base pair in the minor groove of mixed base pair sequences of the type AAAGTTT. NMR spectroscopy reveals the presence of major and minor species of the bound compound. To understand the principles that determine the binding affinity and orientation in mixed sequences of DNA, over thirty DNA hairpin substrates were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 49 publications
(45 reference statements)
2
49
0
Order By: Relevance
“…[14] Similarly, B5 and B6 phenyl protons also show strong intermolecular NOE contacts with the imino proton of G5 in the DNA-DB2277 complex (Table 1). The assignments for the strong intermolecular cross peaks observed between the H2 of adenine and phenyl protons of DB2277 in NOESY spectrum are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[14] Similarly, B5 and B6 phenyl protons also show strong intermolecular NOE contacts with the imino proton of G5 in the DNA-DB2277 complex (Table 1). The assignments for the strong intermolecular cross peaks observed between the H2 of adenine and phenyl protons of DB2277 in NOESY spectrum are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 98%
“…A single and selective binding orientation of the DB2277-DNA complex is observed in imino proton spectra with single resonance peaks for each base pair (Figure 2). [14] 1D proton NMR experiments of the DNA hairpin with 15 N-labeled central G in the –AAGATA– binding site were conducted with DB2277 and reported previously. [14] The findings from this experiment along with 1D NOE experiments conducted on the DB2277-DNA complex allow the assignment of the peak at 11.5 ppm to a downfield shifted aza-benzimidazole-NH (BI -NH) proton signal of DB2277.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that DB2120 with a central pyridine linker unit flanked by phenyl-benzimidazole-based modules for AT recognition (Figure 1) could strongly and selectively recognize a single G base in a G·C bp flanked by AT sequences with an nM affinity (31). It is an important new design finding and complements other new minor groove binders that can also target mixed sequences of DNA (35, 36). These compounds provide strong evidence that new heterocyclic derivatives, with appropriate positioning of H-bond acceptors to interact with the G amino -NH which projects into the minor groove, can be successfully designed.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Furthermore, rational design of azaBI-based DNA minor groove binders led to morphing traditional BI recognition of DNA from AT specific 1215 to guanine (G)-containing sequence specific (Figure 1) by introducing the aza group. 1618 This represents a key milestone showing that small molecules can be structured to recognize any given sequence on DNA. Targeting DNA at specific sequences augments a therapeutic strategy of controlling gene expression as a venue for treating many intractable diseases.…”
mentioning
confidence: 99%